2022
DOI: 10.1007/s40670-022-01604-y
|View full text |Cite
|
Sign up to set email alerts
|

Can an Arts Course Help Mitigate Medical Student Burnout?

Abstract: Introduction Burnout in healthcare providers begins early, with about half of medical students experiencing symptoms of burnout, and as many as one-quarter experiencing depression. While organizational, systemic-level changes certainly contribute to mitigation, organizationally sponsored individual-level changes may also play a significant role. Although the nature of the burnout epidemic and its impact on trainee wellness is fairly well understood, and interventions have been studied, there remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“… 31 Volpe and coauthors noted an decrease in clinician reported stress. 26 Another study compared a brief coloring book intervention with therapy dog exposure and saw decreases in salivary cortisol levels and self-reported stress levels, but the results were not statistically significant. 23 …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“… 31 Volpe and coauthors noted an decrease in clinician reported stress. 26 Another study compared a brief coloring book intervention with therapy dog exposure and saw decreases in salivary cortisol levels and self-reported stress levels, but the results were not statistically significant. 23 …”
Section: Resultsmentioning
confidence: 98%
“…The authors also noted that 6 studies used a control group to assess the association of stress or burnout with the art intervention. 16,18,[23][24][25][26] The other studies used non-participants from the same clinical groups as controls.…”
Section: Impact On Burnoutmentioning
confidence: 99%
“…Expand their scope of vision 6. Strengthening capacity to tolerate ambiguity [ 155 158 ] Online mental health education 1. Skills for independent living 2.…”
Section: Resultsmentioning
confidence: 99%
“…[ 2 – 7 , 55 , 56 , 63 65 , 67 , 70 73 , 76 , 80 85 , 88 – 91 , 94 97 , 111 , 112 , 114 , 115 , 119 , 120 , 122 , 124 , 125 , 130 132 , 136 , 137 , 139 , 143 145 , 154 , 155 , 157 , 158 , 161 , 165 167 , 170 , 172 174 , 177 , 180 , 184 , 187 , 188 ]…”
Section: Resultsunclassified
“… 7 Exposure to art or participation in group-based creative writing workshops can improve anxiety and depressive symptoms and be protective against burnout. 8 , 9 …”
mentioning
confidence: 99%